(untitled) (Eurasian Research Bulletin, 2024)
In this article, the issues of effective use of the improvement of the mechanisms for determining cadastral values for the purpose of taxation in our republic in recent years, as well as the implementation of measures to determine cadastral values by tax authorities using tax administration instruments and eliminate violations, timely disclosure of tax evasion schemes, tax scientific-practical conclusions and suggestions for further optimization of the administration, elimination of contradictions in legal documents have been developed.